1-[2-(1-Hydroxycyclohexyl)-2-(4-methoxyphenyl)ethyl]dimethylammonium chloride (venlafaxine hydrochloride) - Vega, Daniel (2000)
The crystal structure of racemic venlafaxine hydrochloride, C17H28NO+2·Cl¯, consists of two types of parallel chains formed by translated venlafaxine+ cations, hydrogen bonded by Cl¯ anions, and characterized by the opposite chirality of their constituent molecules. These chains organize in two different types of broad layers of opposite handedness, related by a glide plane.